THE ALTERATION OF ATMOSPHERIC PRECIPITATIONS MODE IN THE CENTRAL CAUCASUS REGION WHEN CARRYING OUT ANTI-HAIL PROTECTION ACTIVITIES - M. R. Vatiashvili (Наука. Инновации. Технологии)
Introduction: the review of evaluation of influence of production anti-hail protection of ag- ricultural crops on the atmospheric precipitations mode of the protected and check-out areas, carried out in the Central Caucasus region with the application of: artillery and rocket seeding technology, combined method, competition as well as precipitating acceleration and shock impact methods, is made. Materials and Methods: long-standing experiments and reports on affecting hail processes and man-made atmospheric precipitation augmentation; fragments of hail preventing and interrupting; total values of influence parameters and radar parameters of clouds; weather stations and radio-locators; combined method, competition as well as atmospheric precipitating acceleration and shock impact methods; nonparametric statistical methods. Discussion and conclusions: